Regioselective Oxidation of Lauric Acid by CYP119, an Orphan Cytochrome P450 from Sulfolobus acidocaldarius - LIM, Young-Ran; EUN, Chang-Yong; PARK, Hyoung-Goo; HAN, Songhee; HAN, Jung-Soo; KYOUNG SANG CHO; CHUN, Young-Jin; KIM, Donghak (Journal of microbiology and biotechnology, 2010)
Archaebacteria Sulfolobus acidocaldarius contains the highly thermophilic cytochrome P450 enzyme (CYP119). CYP119 possesses stable enzymatic activity at up to 85 degrees C. However, this enzyme is still considered as an orphan P450 without known physiological function with endogenous or xenobiotic substrates. We characterized the regioselectivity of lauric acid by CYP119 using the auxiliary redox partner proteins putidaredoxin (Pd) and putidaredoxin reductase (PdR). Purified CYP119 protein showed a tight binding affinity to lauric acid (K(d)=1.1+/-0.1 microM) and dominantly hydroxylated (omega-1) position of lauric acid. We determined the steady-state kinetic parameters; k(cat) was 10.8 min(-1) and K(m) was 12 microM. The increased ratio to omega-hydroxylated production of lauric acid catalyzed by CYP119 was observed with increase in the reaction temperature. These studies suggested that the regioselectivity of CYP119 provide the critical clue for the physiological enzyme function in this thermophilic archaebacteria. In addition, regioselectivity control of CYP119 without altering its thermostability can lead to the development of novel CYP119-based catalysts through protein engineering.